2010
DOI: 10.1007/s11064-010-0325-x
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes Express N-Methyl-D-Aspartate Receptor Subunits in Development, Ischemia and Post-Ischemia

Abstract: The expression of the N-methyl-D-aspartate receptor (NMDA-R) in astrocytes is controversial. The receptor is commonly considered neuron-specific. We showed that astrocytes in primary cultures differentially expressed mRNA of NMDA-R subunits, NR1, NR2A and NR2B, in development, ischemia and post-ischemia. One-week-old cultures expressed detectable NR1 mRNA, which fell significantly at 2 weeks and became barely detectable at 4 weeks. NR2A and NR2B mRNA were both significantly up-regulated from 1 to 2 weeks. In 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 66 publications
(83 reference statements)
1
22
0
Order By: Relevance
“…Extraordinarily, they observed that SNP induced GluN2B localization in the cell nucleus, supporting previous findings suggesting putative NMDAR nuclear translocation [115,116]. On the other hand, Zhou et al [117] characterized NMDAR subunit expression in mouse cultured astrocytes at different times and in a model of ischemia. They found GluN1, GluN2A, and GluN2B expression by RT-PCR and immunofluorescence (only GluN1 and GluN2B).…”
Section: +supporting
confidence: 72%
“…Extraordinarily, they observed that SNP induced GluN2B localization in the cell nucleus, supporting previous findings suggesting putative NMDAR nuclear translocation [115,116]. On the other hand, Zhou et al [117] characterized NMDAR subunit expression in mouse cultured astrocytes at different times and in a model of ischemia. They found GluN1, GluN2A, and GluN2B expression by RT-PCR and immunofluorescence (only GluN1 and GluN2B).…”
Section: +supporting
confidence: 72%
“…Overactivity of NMDARs results in excitotoxicity that may activate microglia (Chang et al, 2008). In addition to presence of NMDARs in neuronal population, a report suggests the presence of NMDARs in development, ischemia and post-ischemic events (Zhou et al, 2010). The studies on animal subjects clearly indicate the involvement of astrocytic glutamate receptor in glial cell signaling (Schipke et al, 2001; Wong, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For primary cells, ABCA7-deficient mice (ABCA7Ϫ/Ϫ) were cross-bred with TgCRND8 (ABCA7ϩ/ϩ) mice. Primary cultures were prepared from brain of either embryonic 16-day-old (cortical neurons) or postnatal 1-dayold (astrocytes and microglia) mice according to the method of Cole and de Vellis (22), and mixed glial cells were cultured as described previously (23,24). After 20 -24 days of culturing, microglia were harvested by mild trypsinization (25).…”
Section: Methodsmentioning
confidence: 99%